2015
DOI: 10.1080/15384101.2015.1064567
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B3 controls anaphase onset independent of spindle assembly checkpoint in meiotic oocytes

Abstract: Cyclin B3 is a relatively new member of the cyclin family whose functions are little known. We found that depletion of cyclin B3 inhibited metaphase-anaphase transition as indicated by a well-sustained MI spindle and cyclin B1 expression in meiotic oocytes after extended culture. This effect was independent of spindle assembly checkpoint activity, since both Bub3 and BubR1 signals were not observed at kinetochores in MI-arrested cells. The metaphase I arrest was not rescued by either Mad2 knockdown or cdc20 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…14 Our results show that inhibition of anaphase initiation accompanies the downregulation of homologous genes encoding APC Cdc20 -Esp1 and SAC protein in cyc17D cells. This finding supports previous reports that cohesion resolution is regulated by a SAC-independent pathway during meiosis, 17,37,41 and suggests that Esp1 downregulation may be responsible for the cyc17D phenotype ( Fig. 4C and 4D).…”
Section: Cyc17 Is Essential For Chromosome Segregationsupporting
confidence: 93%
See 1 more Smart Citation
“…14 Our results show that inhibition of anaphase initiation accompanies the downregulation of homologous genes encoding APC Cdc20 -Esp1 and SAC protein in cyc17D cells. This finding supports previous reports that cohesion resolution is regulated by a SAC-independent pathway during meiosis, 17,37,41 and suggests that Esp1 downregulation may be responsible for the cyc17D phenotype ( Fig. 4C and 4D).…”
Section: Cyc17 Is Essential For Chromosome Segregationsupporting
confidence: 93%
“…36 A recent study in mice showed that Cyclin B3 controls anaphase onset in meiotic oocytes. 37 These reports suggest that Cyc17 might also be involved in meiosis in T. thermophila.…”
Section: Resultsmentioning
confidence: 97%
“…CycA and CycB are required together to achieve a proper metaphase. CycB3 appears to be the major driver of anaphase, and may function in this respect by promoting APC/C activity (McCleland et al 2009; Yuan and O’Farrell 2015), a function that appears to be conserved (Deyter et al 2011; Zhang et al 2015). Therefore, the cyclins are collectively essential for mitosis but they show considerable overlap in their individual contributions.…”
mentioning
confidence: 99%
“…2009), while expression studies in mammals point to a meiosisspecific function (Nguyen et al, 2002). Interestingly, loss-offunction analysis has consistently revealed an anaphase function for cyclin B3, as both mitotic and meiotic cell cycles show a metaphase arrest (van der Voet et al, 2009;Deyter et al, 2010;Zhang et al, 2015); however, in some cases the metaphase arrest is dependent on the spindle assembly checkpoint (SAC) (Deyter et al, 2010) whereas in others it is not (Zhang et al, 2015). Even within C. elegans the exact role of CYB-3 during mitosis has been difficult to pin down.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of CYB-3 causes a more severe delay in NEB, and cells then arrest at metaphase (Cowan and Hyman, 2006;van der Voet et al, 2009;Deyter et al, 2010). Thus, as is the case for cyclin B3 proteins in other organisms (Yuan and O'Farrell, 2015;Zhang et al, 2015), CYB-3 is required to promote anaphase. Interestingly, work in C. elegans has revealed additional functions for CYB-3 prior to mitotic entry (Deyter et al, 2010).…”
Section: Introductionmentioning
confidence: 99%